LABORATORY BIOMARKERS OF VITAMIN B12 DEFICIENCY ANEMIA - Berdiyarova Sh.Sh,; Nabiyeva F.S.,; Yakubova Ch,; Tojieva M.Kh, (TADQIQOTLAR, 2026)
Annotation. Vitamin B12 is a B vitamin that has an important role in cellular metabolism, especially in DNA synthesis, methylation and mitochondrial metabolism. Clinical B12 deficiency with classic haematological and neurological manifestations is  relatively uncommon.  However,  subclinical  deficiency  affects between  2.5%  and 26% of the general population depending on the definition used, although the clinical relevance  is  unclear.  B12  deficiency  can  affect  individuals  at  all  ages,  but  most particularly  elderly  individuals.  Infants,  children,  adolescents  and  women  of reproductive age are also at high risk of deficiency in populations where dietary intake of B12-containing animal-derived foods is restricted. Deficiency is caused by either inadequate  intake,  inadequate  bioavailability  or  malabsorption.  Disruption  of  B12 transport  in  the  blood,  or  impaired  cellular  uptake  or  metabolism  causes  an intracellular deficiency. Diagnostic biomarkers for B12 status include decreased levels of circulating total B12 and transcobalamin-bound B12, and abnormally increased levels  of  homocysteine  and  methylmalonic  acid.  In  this  research,  we  will  discuss vitamin  B12 deficiency,  various  diagnostic  tests,  and  an  algorithm  used  in  the investigation of vitamin B12 deficiency.